All Questions Topic List
Differentiation Questions
Previous in All Question Next in All Question
Previous in Differentiation Next in Differentiation
Question Number 60357 by Sardor2211 last updated on 20/May/19
Commented by Mr X pcx last updated on 20/May/19
theequationisnotclearbutisupposethatis(1+x2)y′−2xy=(1+x2)2(he)⇒(1+x2)y′−2xy=0⇒(1+x2)y′=2xy⇒y′y=2x1+x2⇒ln∣y∣=ln(1+x2)+c⇒y=k(1+x2)mvcmrthodgivey′=k,(1+x2)+2xk(e)⇒(1+x2)k′(1+x2)+2xk(1+x2)−2xk(1+x2)=(1+x2)2⇒k′=1⇒k(x)=x+λ⇒y(x)=(1+x2)(x+λ)⇒y(x)=x3+x+λ(1+x2)weseethatyisapolynom..
Terms of Service
Privacy Policy
Contact: info@tinkutara.com